Pertumbuhan Ekonomi, Distribusi Pendapatan dan Lingkungan - Suparmoko, M. (Unisia, 2016)
The goal of the economy development is to increase the welfare of a nation. The welfare is often indicated by the low or the high of the country’s income per capita. However, recently the environmental factor should be included in the formulation of the income per capita of a country as a green national income. Firstly, this paper discusses the relationship between the income per capita and the income distribution. Secondly, the discussion includes the assessment of the income distribution imbalance focusing on the aspects of imbalance Ratio, Lorenz Curve, and Gini index. Lastly, Kuznet Curve is crucial to be used in the economic development analysis as an environmental factor in the income per capita of a country.